Forensic and chemometric approaches in distribution, characterization and health risk assessment of polycyclic hydrocarbons in selected aquaculture farms in Peninsular Malaysia - Retnam, Ananthy (2013)
This is a pioneering study and report on polycyclic aromatic hydrocarbons (PAHs) in aquaculture ecosystem in Malaysia. In this study the occurrence of PAHs in sediments, oysters, fish and fish feed were examined and the health risk assessment was conducted. Samples were collected from selected aquaculture farms in Peninsular Malaysia from January 20 10 to November 20 II inclusive of remote and polluted areas. The results revealed the average concentration of total PAHs in sediment ranged from 20 to 184 L oysters 121 to 519, fish 22 to 228 and fish feed 150 to 366 ng/g dry weight. The levels of PAHs reflect human activities, with higher concentrations observed in industrial zones. pOI1 areas and urban settlements. Application of forensic and chcmomctric techniques on sample data revealed that the sediments collected from aquaculture farms and periphery were dominated by pyrogenic sources from vehicle emission (54°0) and biomass burning (9°0) while petrogenic sources coming from petroleum oil (37%). The profile of PAHs obtained from fish and oyster farm sediments differ significantly (p < 0.(5) implying additional pollution sources into fish limn. Enrichment of organic carbons, nitrogen and PAHs in fish farms revealed an average of 2R.7%,4.65% and 156% respectively. Enrichment of TOe is statistically significant to the enrichment of total PAHs, carcinogenic PAHs and 4-6 ring PAHs but not 2-3 ring PAHs. The compound benzot ajpyrcne was detected in all samples. This study found that accnaphthylcnc, fluoranthene and dibenzotahjanthracenc concentrations were higher than the permissible levels in interim sediment quality guidelines. This might be harmful to aquatic animals and to human who consume them. The body burden of PAHs in oysters fall within moderate range and is comparable to other studies in bivalves. Temporal variation due to spawning was evident in oysters at Pulau Betong Batu Lintang and Pasir Panjang. PAHs in edible fish tissues range between low to moderate. Normalization of total PAHs with lipid content drew a meaningful result compared to dry weight normalization. Strong signi ficant correlation was observed between lipid normalized total PAHs and total toxicity equivalence concentrations (p < 0.05 vs. p > 0.05). Fish Iced samples were dominated by high molecular weight PAHs. The profile of PAHs in fish feed were similar regardless of locations, types and lipid content. PAHs concentrations were found to be higher or in par with other studies worldwide. Cluster analysis and discriminant analysis implied that fish ICed was the main source of PAHs in edible fish tissue. Non-cancer risk assessment of PAHs in sediment, oyster and fish showed that the values were below the concern levels published by USEPA. Cancer risk due to consumption of red snapper from Jclutong and sea bass lrorn Jclutong and Gclang Putah is higher than the safe levels recommended for all groups of population under study. Overall PAHs from vehicular emission dominated aquaculture sediment. The consumption of cultured scabass and red snapper from Jclutong and scabass from Gclang Patah are not safe for all group of populations.